Prevalence of Amputation Events in Diabetic Ulcer Patients at Tarakan District Hospital - Ruchika, Ruchika; Oktavia, Eva; Kartadinata, Riki; Wijaya, Jefry; Ratu, Livia Lita (Jurnal MedScientiae, 2023)
Diabetes mellitus (DM) is a condition of increased blood sugar levels that can increase the risk ofmacrovascular and microvascular damage, thereby reducing the quality of life of the sufferer.Objective is to determine the prevalence, demographic data and clinical data from diabetic ulcerpatients who performed amputations at Tarakan Hospital for the period of 2018. The researchsubjects were patients with diabetes mellitus who had diabetic ulcers who were amputated at TarakanHospital for the period 2018. Data on the results of amputation of diabetic ulcer patients werecollected and the researchers set aside forms that included exclusion criteria. Furthermore, dataprocessing using SPSS statistical programs and Microsoft excel. The total sample was obtained by 8samples with amputations from 398 samples at the Tarakan Hospital for the period 2018. The mostages were 17-60 (62.5%) as many as 5. The highest gender was female (62.5%) as many as 5 people.Smoking only 12.5% ​​as much as 1 person. Dyslipidemia obtained 50% as many as 4 people.Hypertension was obtained 62.5% as many as 5 people. The longest duration of suffering from DMwas > 10 years (62.5%) as many as 5 people. Obesity who experienced diabetic ulcer amputation asmany as 4 people (2.0%). Patients aged 17-60 experienced the most amputation of diabetic ulcers.Female, dyslipidemia, hypertension, duration of DM > 10 years, obesity